Influence of process parameters on the adsorption properties of zeolite 13X - Ognjen Stojkić; Radislav Filipović; Mladen Janković; Duško Kostić; Mitar Perusic; Srećko Stopić; Vladimir Damjanović (Journal of Chemists, Technologists and Environmentalists)
Zeolite 13X is one of the best adsorbents among zeolites and one of the most commercially available zeolites.  This paper investigates the influence of several process parameters on the properties of 13X zeolite, including crystallization temperature, crystallization duration and Si/Al molar ratio in the starting reaction mixture. The quality of the obtained powders was examined in detail through a series of analytical and instrumental methods, presented in the paper. Water and CO2 adsorption capacities were determined as key quality parameters of 13X zeolite, and additional characterization was performed by determining material granulometry, specific surface area (BET analysis), crystallinity (X-ray diffraction method) as well and SEM analysis. The obtained results indicate a clear dependence between the examined process parameters of the system and the characteristics of the synthesized materials, thus enabling the selection of optimal conditions for the synthesis of 13X zeolite.